Continuous Professional Development and the Dynamics of Teacher Professionalism - Pepen supendi; Dewi, Septiani Maria; Lutpi Pauji Ismail; Pitria Pebrianti; Atip Purnama (LETIGES, 2026)
This study aims to analyze the implementation of Continuous Professional Development (CPD) in strengthening teacher professionalism in Madrasah Aliyah Negeri (MAN) throughout West Java. The study used a qualitative approach with a multi-site case study design in several purposively selected MAN. The researchers collected data through in-depthinterviews, observations, and documentation studies, then analyzed them using thematic analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of CPD has been carried out through various internal and external activities, such as Musyawarah Guru Mata Pelajaran (MGMP), In-House Training, academic supervision, and technology-based learning training. CPD contributes to strengthening professional knowledge, pedagogical and technical skills, as well as the formation of professional attitudes of teachers who are more reflective, disciplined, and open to learning evaluation. However, the effectiveness of CPD implementation is still influenced by program planning that is not fully based on teacher needs, limited post-training mentoring, and inconsistent implementation of training results. This study also shows that a collaborative culture, madrasah institutional support, and professional learning communities play an important role in supporting the sustainability of teacher professional development. This research contributes to strengthening the understanding that CPD is not only related to improving technical competence but also to the holistic development of teacher professionalism in the context of Islamic education. The implications of this research emphasize the importance of developing needs-based CPD, strengthening ongoing mentoring systems, and impact-based evaluation of learning practices